2018
DOI: 10.14748/ssmd.v1i1.5195
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Ginigval Health in Children With Crown Restorations

Abstract: INTRODUCTION: Prosthetic treatment with fixed constructions is an effective method for recovering severely destroyed teeth. The purpose of this study is to track the changes in the gingival tissues around teeth, which are prosthetically treated with different aesthetic crowns. MATERIALS AND METHODS: Eighty-two teeth were studied with 46 of them being restored with CAD/ CAM composite crowns and 36 with ready-made zirconia crowns. The assessment of the condition of the surrounding soft tissues was performed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
1
Order By: Relevance
“…Time-dependent relationship between plaque index (PI), gingival index (GI) and bleeding on probing index (BOP) scores for posterior zirconia crowns (NuSmile AND CAD/CAM). The current study also differed from Dimitrova 2018, which showed an improvement in the gingival health (MGI) of pre-made CAD/CAM crowns and NuSmile® crowns between the pre-treatment and follow-up phases of 2 weeks, two months, six months, and one year [18].…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Time-dependent relationship between plaque index (PI), gingival index (GI) and bleeding on probing index (BOP) scores for posterior zirconia crowns (NuSmile AND CAD/CAM). The current study also differed from Dimitrova 2018, which showed an improvement in the gingival health (MGI) of pre-made CAD/CAM crowns and NuSmile® crowns between the pre-treatment and follow-up phases of 2 weeks, two months, six months, and one year [18].…”
Section: Discussioncontrasting
confidence: 80%
“…The current study also differed from Dimitrova 2018, which showed an improvement in the gingival health (MGI) of pre-made CAD/CAM crowns and NuSmile® crowns between the pre-treatment and follow-up phases of 2 weeks, two months, six months, and one year [ 18 ].…”
Section: Discussionmentioning
confidence: 73%